REVIEW ON ASSESSMENT OF DEPRESSION BY BECK DEPRESSION INVENTORY (BDI) AND HAMILTONDEPRESSION RATING SCALE (HDRS) - Shahlaei, Leili; Hasan, Shahizan; Ahmad, Norshafrin; Kiumarsi, S. (International Journal of Research -GRANTHAALAYAH, 2014)
The study aimed at investigating how to apply two familiar tools formeasuringdepression among diabetic patients in Iran. The study discusses about two inventories and emphasizes that depression is such an important issue that needs to receive a great deal of attention in order to create grounds to be prevented or cured. The issue of concept of tools was also discussed in the study. The discussion in the paper is based on the conceptual framework of Beck Depression Inventory (BDI) and Hamilton Depression Rating Scale (HDRS).Thesetools are appropriate for the study because they allowthe reader to understand how to measureand identify symptoms of depression. The paper recommends that the tools should be carefully applied in order to improve mental health and reduce the prevalence of depression.